Holistic Water-Energy-Food Nexus for Guiding Water Resources Planning: Matagorda County, Texas Case - Kulat, Muhammed I.; Mohtar, Rabi H.; Olivera, Francisco (Frontiers in Environmental Science, 2019)
Nations, particularly those with well-established infrastructure, have started to look for new, innovative solutions to address the expected, inevitable high demand for primary resources. The WEF (water–energy–food) Nexus approach, which holistically considers the dynamic interlinkages between water, energy, and food resources, has come to the forefront within scientific and practice communities. Supporters assert that sustainable solutions can be revealed though the use of this approach, rather than conventional approaches that often overlook the interlinkages. The authors developed a holistic framework to provide sustainable scenarios that include feasible infrastructure interventions. The framework focuses on water, includes a unique analytic tool for quantifying scenarios, and ultimately produces a sustainability analysis of each scenario. Optimal scenarios are offered that consider site-specific dynamic resource interlinkages. The platform was applied to the case study of Matagorda County, Texas, identified as one of the most water-stressed regions in the state of Texas by the Texas Water Development Board, the state’s executive agency for water resources management. High demands from energy and agriculture sectors in the county and sharp population increase in the upper basins, which include the city of Austin, have put great pressures on the water resources of Matagorda County. Farmers have been forced to change their crops from high to lower water-demand crops, in spite of apparent and relatively abundant local water resources. The findings of the case study present a most sustainable scenario, including infrastructure interventions that will increase the annual income of agriculture sector from $188 million to $239 million. The approach also helps preserve resources while reducing annual water and energy demand by 22 million m3 and 21 million kWh, respectively, and does not sacrifice on-going municipal and industrial water use or energy production in Matagorda, Texas.